Product, Service & Business Model Innovation Amid New Challenging Regulation: Case Study of a Construction Company in Indonesia - Rizko Pradana Andika (Green Publisher Indonesia, 2025)
The construction industry is undergoing significant transformations due to economic, technological, and market factors. PT ABC, a subsidiary of DEF, specializes in innovative and sustainable construction solutions. The company faces challenges due to its heavy reliance on the Local Government Infrastructure Institution , which contributes over 70% of its revenue. Additionally, government regulations favoring Micro, Small, and Medium Enterprises (MSMEs) have intensified competition, necessitating strategic innovation. To maintain competitiveness, ABC is exploring two business solutions: soil stabilization and concrete repair. This research aims to compare these business models, determine the most suitable solution for the Local Government Infrastructure Institution , and develop an effective business development strategy. The study employs qualitative methods, including VRIO, SWOT, and TOWS analysis, as well as the Business Model Canvas framework. The findings suggest that soil stabilization offers higher market potential due to its cost efficiency and alignment with government priorities for sustainable infrastructure. The study provides strategic recommendations for ABC to enhance its market position through innovation, operational efficiency, and strengthened client relationships.